ESTUDO DAS CÉLULAS MEIÓTICAS EM EXEMPLARES DE STALEOCHLORA HUMILIS (REHN, 1909) (ORTHOPTERA, ROMALEIDAE) DO MUNICÍPIO DE CAMPO GRANDE, MS. - Hugo Vernochi Rosa, Victor; Gonzalez Gouveia, Juceli; Maria de Rossi Vieira, Margarida (ANAIS DO ENIC, 2026)
-